STRATEGI MADRASAH IBTIDAIYAH DALAM MENINGKATKAN PROFESIONALISME GURU KELAS DI ERA REVOLUSI INDUSTRI 4.0 - Bela Vita Rismawati; Muhamad Arif; Muhammad Mahfud (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2021)
Professionalism for Elementary School / Madrasah Ibtidaiyah teachers is a necessity that must be possessed, in the presentation of professionalism for teachers there are four minimum competencies, namely pedagogic, professional, social and personality. Basically, the discussion about teacher professionalism is actually very clear in the "Minister of Education Regulation No. 16 of 2007 on Academic Qualification Standards and Teacher Competencies. However, the world of education faces quite a tough challenge, when it enters the era of the industrial revolution 4.0. the position of the teacher is a key position in guarding the success of learning in the midst of digitalization. So, the only thing that can be done is to continuously improve its competence. This research seeks answers from the strategy of the Miftahul Ulum Kesamben Wetan Islamic school in increasing professionalism in the era of the industrial revolution 4.0. This research uses a qualitative case study method with data collection techniques through interviews, observation and documentation, and is supported by data analysis from miles and hubarman. The results showed that the strategy of Madrasah ibtidaiyah Miftahul Ulum Kesamben Wetan Driyorejo Gresik, in improving teacher professionalism in the 4.0 revolution era, includes: (1) IT-based training, (2) Education Seminar, (3) Learning workshop in the era of industrial revolution 4.0, (4) ) Education and learning workshops in the digital era, (5) Madrasah supervision carried out by the principal of madrasah ibtidaiyah, (6) Bimtek held by madrasah, (7) Encouraging and motivating teachers to join Teacher Working Groups (KKG), (8) ) Conducting Comparative Studies to higher quality institutions, (9) Conducting social services to around madrassas and communities in need. (10) Workshop with local kyai to strengthen the struggle, (11) Reciting together in collaboration between Madrasah Ibtidaiyah and LP Maarif NU Driyorejo.